2023
DOI: 10.1111/cpr.13438
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p38 MAPK signalling in intervertebral disc degeneration

Abstract: Intervertebral disc degeneration (IVDD) is a common degenerative disease mediated by multiple factors. Because of its complex aetiology and pathology, no specific molecular mechanisms have yet been identified and no definitive treatments are currently available for IVDD. p38 mitogen‐activated protein kinase (MAPK) signalling, part of the serine and threonine (Ser/Thr) protein kinases family, is associated with the progression of IVDD, by mediating the inflammatory response, increasing extracellular matrix (ECM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The MAPK signaling pathway is involved in inflammation, cell growth and differentiation, the cell cycle, and cell death. [ 39 ] Activated MAPK inhibits claudin-2 expression, resulting in increased intestinal mucosal permeability, release of large amounts of pro-inflammatory factors, and promotion of intestinal epithelial cell death. [ 40 , 41 ] TNF-α is a monokine produced by macrophages and monocytes, which promotes the development of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway is involved in inflammation, cell growth and differentiation, the cell cycle, and cell death. [ 39 ] Activated MAPK inhibits claudin-2 expression, resulting in increased intestinal mucosal permeability, release of large amounts of pro-inflammatory factors, and promotion of intestinal epithelial cell death. [ 40 , 41 ] TNF-α is a monokine produced by macrophages and monocytes, which promotes the development of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway can mediate the activation of the ERK, p38, and c -JNK signaling pathways, respectively. Among them, the most widely studied in the field of IDD are ERK and p38 downstream signaling pathways [ 55 , 56 ]. A growing number of studies have reported that MAPK signaling is closely related to matrix synthesis and ECM degradation during IDD progression [ 57 ].…”
Section: Introductionmentioning
confidence: 99%